The relationship code : deciphering genetic and social influences on adolescent development - Reiss, David (Adolescent lives ;, 2000)
Introduction: Reconciling social and genetic influences on adolescent development Part 1: Logical tools for analyzing adolescent development Relationships and adolescent development Genetic influences on development Genetic analysis of adolescent development Studying adolescent siblings and their families Part 2: Genes and relationships: Thesis, antithesis, synthesis Thesis I: A theory of adolescents' shared and nonshared family relationships Thesis II: Major findings on adolescents' family relationships Antithesis I: Influences on stability and change in adolescent adjustment Antithesis II: Influences on stability and change in adolescents' families Antithesis III: Linking family relationships and adolescent development Synthesis I: Genetic influences on change in family relationships and adolescent development Synthesis II: The relationship code Synthesis III: Genetically informed portrayals of adolescents and their families Epilogue: The family Appendix A: Explanation of methods for data presented in Chapters 8 through 13 Appendix B: Explanation of results Appendix C: Additional genetic analyses